THE EFFECTS OF ERROR TREATMENT ON INTERLANGUAGE OF INDONESIAN LEARNERS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Endang Fauziati (Universitas Muhammadiyah Surakarta, 2009)
Interlanguage errors always exist in foreign language learning. They become thesource for studying the system of the learners’ interlanguage (IL). Han (2004) reviews hundreds of IL studies and concludes that there are two competing views can be identified. One view suggests that error treatment (ET) has unconvinced value in classroom second language acquisition or SLA (Krashen 1982). Adults do not require constant correction in useful ways; thus, the role of the teacher is to provide comprehensible inputs for the learners to move to the next stage of IL. ET has little value in SLA because IL is fossilized (Mukkatash 1987; Thep-Ackrapong 1990). This view corresponds with Patkowsky (1980), and Johnson and Newport (1989) who believe fossilization is due to CP. The opposite view comes from White (1991), Spada and Lightbown (1993), and Muranoi (2000) who believe that that ET is very important in foreign language (FL) learning. Learners can take a lot of benefits from ET as they can develop their IL system to a higher level of accuracy. This view corresponds with Scovel (1988), White and Genesee (1996), and Bialystok (1997) who deny the existence of CP in SLA; CP may applicable for the acquisition of phonology but not for syntax. Thus, grammar is learnable at any age. This study investigates the effects of a short-term error treatment (ET) on IL errors, with specific attention to the learners’ ungrammatical items. The problem states “what are the effects of a ET on the learners’ ungrammatical items?” Are their ungrammatical items fossilized (in a sense that they are static in nature) or dynamic after the learners have been exposed to the ET? The data were the learners’ free compositions collected four times: prior and after the ET and twomonths afterwards. They were analyzed quantitatively and qualitatively. The result indicates that the ET changed the state of the learners’ ungrammatical items. They became so dynamic. At a certain period, some appeared; then due to the ET, some were destabilized, some were fluctuating, and others were still stabilized. New errors appeared as they started learning to use new grammatical items. The conclusion drawn from this study is that ET can change the state of the learners’ IL errors; ET contributes to the destabilization process. Errors may persist momentarily but they can be destabilized. The ET still works on the learners who are at their post puberty. Thus, there is a great possibility for the learners to acquire complete TL grammar since their ungrammatical items are dynamic.Keywords: error treatment, interlanguage, fossilization, stabilization, destabilization.